(untitled) (African Journal of Biomedical Research, 2022)
This study was aimed at determining the accuracy of placenta thickness and volume among normal singleton pregnancies in Nigerians. In this prospective cross-sectional study, four hundred and twenty-three (423) consenting healthy singleton pregnant women within 13-40weeks gestational age (GA) with regular menstrual cycle and known last menstrual period were recruited and grouped into 27 groups based on their ultrasound GA. All participants had an obstetric ultrasound, and the main outcome variables were placenta thickness, placenta volume, and ultrasound GA. The data generated were analyzed, and P values ≤ 0.05 were statistically significant in this study. Four hundred and eight (408) normal singleton pregnant women with an average age of 29.6(+/-5) years completed the study. One hundred and seventy-seven (43.4%) were between 26-30 years, while 149(36.5%) were aged 31 years and above. The placenta thickness showed a strong positive linear relationship between GA (Y-axis) and placenta thickness (in mm) (x-axis) with a best-fit line of Y -= -0.19 + 1x. The placenta volume values (X) also had a positive but non-linear relationship with the best fit line equation of Y= 11.88 +0.12X – 0.000102X2 between 13 and 40 weeks of pregnancy. There is a linear relationship between placenta thickness and GA and curvilinear relationships between placenta volume and GA. Routine assessment of placenta thickness and volume could serve as an effective alternative means of dating normal pregnancy in women with unreliable dates of the last menstrual period.